Enhancing the dispersability of TiO2 nanorods and gaining control over region-selective layer formation - Etschel, Sebastian; Tykwinski, Rik; Halik, Marcus (Langmuir, 2016)
We demonstrate that the dispersibility and reactivity of core-shell TiO2 nanorods (NRs) can be controlled significantly through functionalization with a combination of ligands based on phosphonic acid derivatives (PAs). Specifically, a glycol based PA allows dispersion of the NRs in methanol (MeOH). On the other hand, incorporating an alkyne terminated PA in the ligand shell of the NRs allows for a copper-catalyzed alkyne-azide cycloaddition (CuAAC) reaction with an azide-patterned aluminum oxide (AlOx) substrate and forms a region-selectively deposited film of NRs. We clearly demonstrate that the quality of the NR films correlates strongly with the stability of the NR dispersions in the reaction medium. In particular, tuning the concentration of alkyne PA in the ligand shell inhibits aggregation of the NRs on the substrate, while reactivity for the CuAAC reaction is maintained. The surface coverage with NRs fits the Langmuir model. This study illustrates that surface functionalization of AlOx substrates can be effectively and conveniently controlled through enhancing the dispersibility of the NRs using mixed ligand shells.